دور إدارة مخاطر المشروعات في جودة اتخاذ القرارات دراسة مسحية على شركات المقاولات العاملة في الساحل السوري - ديوب, محمد; زريقة, ولاء (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى دراسة أثر أبعاد إدارة مخاطر المشروعات في شركات المقاولات العاملة في الساحل السوري على جودة اتخاذ القرارات وتحديد البعد الأكثر تأثيراً وأهمية في تفسير هذه الجودة. قام الباحث بإتباع المنهج المسحي في دراسته، وقد شمل مجتمع الدراسة كافة شركات المقاولات العاملة في الساحل السوري، وبلغ حجم عينة الدراسة 75 وحدة معاينة. استخدم الباحث مقياساً لمستوى نضج إدارة مخاطر المشروعات مصمماً من قبل (Ciorciari & Blattner, 2007)، ومقياساً آخر لجودة اتخاذ القرارات مصمماً من قبل (Donelan, 2013).تبين من خلال الدراسة أن هناك علاقة إيجابية وهامة بين تحديد الأحداث والمخاطر المستقبلية وجودة اتخاذ القرارات، ويحتل هذا المؤشر المرتبة الأولى بين أبعاد إدارة مخاطر المشروعات من حيث التأثير على جودة اتخاذ القرارات حيث يفسر ما نسبته (9.61%) من هذه الجودة، كما أن العلاقة بين المتغير التابع (جودة اتخاذ القرارات) وأبعاد إدارة مخاطر المشروعات السبعة الباقية والمتمثلة ب (الرقابة على إدارة المخاطر - الرد على المخاطر - تحديد الأهداف - تقييم المخاطر - التحكم بالنشاطات - ثقافة إدارة المخاطر - المعلومات والتواصل) هي علاقة إيجابية وهامة، وإدارة المخاطر ككل تفسر ما نسبته (22.6%) من جودة اتخاذ القرارات. استناداً إلى نتائج البحث نوصي بضرورة أن تقوم شركات المقاولات العاملة في الساحل السوري بنشر ثقافة إدارة المخاطر في كافة المستويات الإدارية لديها بالشكل الذي يعزز من تطبيق عمليات إدارة مخاطر المشروعات بشكل صحيح، لأن ذلك سينعكس على اتخاذ قرارات أكثر جودة فكلما كان هناك إدارة مخاطر فعالة قلت حالات عدم التأكد والمخاطرة بشأن المستقبل وارتفعت جودة اتخاذ القرارات.Project risk management plays a pivotal role in the decision-making process, this research aims mainly to study the impact of the dimensions of project risk management in contraction firms operating in the Syrian coast on the quality of decision-making and to identify the most influential dimension in the interpretation of this quality. The researcher had followed the survey method in his study, and the study population was included all construction companies operating in the Syrian coast. The researcher adopted probability sampling (random sampling), and the study sample size was 75 units. The researcher used a measure of the maturity level of project risk management that developer by (Ciorciari & Blattner, 2007), and another instrument to measure the quality of decision-making designed by (Donelan, 2013). The findings of this study shows that There is significant positive relationship between events identification and the quality of decision-making and events identification variable occupies first place among project risk management dimensions in terms of impact on decision making quality, because this dimension explains a rate equal (9.61%) of decision making quality. The relationship between the dependent variable quality of decision-making and the seven remaining dimensions of risk management projects namely (monitoring of risk management - risks response - objective setting - risk assessment - control activities - risk management culture - information and communication) is a positive and significant relationship, and risk management as a whole explain what percentage of (22.6%) of the quality of decision-making. The most important recommendations reached by the researcher that the contraction firms working in the Syrian coast should to spread the risk management culture at all levels of management to enhances the application processes PRM because it will reflect on a more quality of decisions making.